Тектонические вертикальные движения и осадочное заполнение бассейнов на син- и пострифтовом этапах развития литосферы - Гончар, В.В. (Геофизический журнал, 2017)
Виконано одновимірне чисельне моделювання ізостатичних реакцій літосфери на термальне піднімання її підошви (активний рифтинг) і поєднане з ним формально незалежне стоншення кори. Обговорено еволюційні криві швидкостей вертикальних рухів і зсувів межі поділу. One-dimensional numerical modeling of isostatic response of lithosphere to thermal uplift of its bottom (active rifting) and interconnected formally independent thinning of the crust has been fulfilled. Evolution curves of vertical movements and interfaces displacements velocities have been examined.